Membangun Jiwa Wirausaha Digital: Cara Mudah Mulai Bisnis Online Sejak SMA di SMA Negeri 1 Payaraman Kabupaten Ogan Ilir - Edduar Hendri; Agus Mulyani; Yasir Arafat; Ilhamsyah Ilhamsyah; Heryati Heryati; Akilah Akilah; Vera Sari; Erfan Robyardi; Reina Damayanti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This Community Service activity aims to increase the understanding and motivation of SMA Negeri 1 Payaraman students in utilizing digital media for entrepreneurship. The program was held on November 18, 2025 and was attended by grade XII students. The methods used include interactive lectures, entrepreneurial motivation, discussions, and evaluation using the Likert scale questionnaire. The material was delivered by eight speakers from the Faculty of Economics and Business, University of PGRI Palembang, including the introduction of digital business, online marketing strategies, business plan preparation, product innovation, and entrepreneurial ethics. The results of the evaluation showed that the participants had a good understanding of the concept of digital entrepreneurship, with an average score in the range of 4.0–4.4. The majority of students were in the category of agree to strongly agree with all evaluation statements, indicating that the activity was effective in fostering digital entrepreneurship literacy and motivation. This program is recommended to be continued through more in-depth applicative training.